Corrosion characteristics of Mo and TZM alloy for plasma facing components in molten lithium at 623 K. (15th May 2022) - Meng, X.C.; Li, L.; Li, C.L.; Andruczyk, D.; Tritz, K.; Maingi, R.; Huang, M.; Zhang, D.H.; Xu, W.; Sun, Z.; Zuo, G.Z.; Hu, J.S.
Abstract: In this study, the corrosion behaviours of molybdenum (Mo) and a Mo-based alloy (TZM) were investigated using a static immersion corrosion technique. Weight loss, surface microstructure, and corrosion depth of Mo and the TZM alloy were correlated with elements. The compatibility of Mo and the TZM alloy in static liquid Li was suitable. Mo demonstrated uniform corrosion with a homogenous dissolution of free C and Mo, and TZM alloy exhibited a nonuniform corrosion behaviour with a preferential grain boundary attack caused by the selective dissolution of free C, Ti, and Zr. When the surface oxidation layer of the samples was consumed, free C from Mo and TZM diffused into molten Li to form Li2 C2 and then was captured by Zr, Ti, and Mo to form thermodynamically stable carbides, which resulted in the enrichment of the C layer near the sample surfaces. In addition, Ti and Zr acted as N-trappers in liquid Li; the formation of Zr and Ti nitrides resulted in the enrichment of N, Ti, and Zr elements on the surface and led to TZM corrosion increase. Thus, Zr and Ti depletion, pitting, and grain boundary corrosion were problematic for TZM under long-term exposure to liquid Li. Reducing the content of free C and nonmetallic N and increasing the amount of Ti and Zr carbides on the surface of and inside the raw TZM alloy helped improve the corrosion resistance of TZM in liquid Li. Highlights: Corrosion behaviors of Mo and TZM exposed to liquid Li at 623 K for 1300 h were investigated and compared. The corrosion mechanism of Mo and TZM in liquid Li was discussed. Mo demonstrates a homogeneous corrosion while TZM shows a nonuniform corrosion. Suggestions to alleviate the corrosion of Mo based alloy in liquid Li were put forward.